2020
DOI: 10.3390/ma13020444
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Collaborative Drag Reduction Effect of Polymers and Surfactants

Abstract: Polymer additives and surfactants as drag reduction agents have been widely used in the field of fluid drag reduction. Polymer additives can reduce drag effectively with only a small amount, but they degrade easily. Surfactants have an anti-degradation ability. This paper categorizes the mechanism of drag reducing agents and the influencing factors of drag reduction characteristics. The factors affecting the degradation of polymer additives and the anti-degradation properties of surfactants are discussed. A mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 51 publications
0
44
0
Order By: Relevance
“…It can be seen that there have been many research works on spider silk and it has obtained preliminary applications in many fields. Spider silk has also been one of the hot research topics in recent years and has shown great application and commercial value in various fields (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that there have been many research works on spider silk and it has obtained preliminary applications in many fields. Spider silk has also been one of the hot research topics in recent years and has shown great application and commercial value in various fields (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al [10] reduced drag by studying the synergistic drag reduction of polymers and surfactants. e above research studies on fluid-structure interaction of the centrifugal pump are all aimed at metal pumps.…”
Section: Introductionmentioning
confidence: 99%
“…In the laser cladding process, there are a series of complex physical and chemical reactions. In this process, not only the composition of the coating material, the performance of the coating material and the performance of the matrix itself, but also the laser process parameters have a significant impact on the quality of the cladding layer [34][35][36].…”
Section: Principle and Characteristics Of Laser Cladding Methodsmentioning
confidence: 99%